FROM CORK WASTE TO ELECTRICAL THERMAL AND HYDROGEN BIOENERGIES - Rafika HELAIMIA (My University, 2023)
Abstract – Several measures have been taken in recent years to reduce the use of fossil fuels and shift toward renewable energy sources such as biomass, particularly cork wastes, which currently generate more than 60% of the energy generated by cork powder energy conversion. This powder’s high calorific content ranging from 4,000 to 7,000 Kcal/kg is natural, renewable, and recyclable, and contributes to a reduction in greenhouse gas emissions and carbon footprint. Cork wastes are now considered strategic substances due to their significant environmental and socioeconomic roles in the worldwide. The present research relies on cork wastes as potential of electrical, thermal, and hydrogen bioenergy source. Cork properties and energy usages are discussed beginning with cork's environmental, economic, and energy properties and processing through two types of cork wates conversion processing: industry and energy process. The firstl one is in four stages: preparation, transformation, granulation, and transformation, whereas the second one has three phases: extraction of cork, storage of planks, and from micro agglomerated cork stoppers to energy generation, and at the end of the study the three types of bioenergy that cork wastes may produce based on recent academic and research discoveries. Electrical energy, thermal energy, and hydrogen energy are the three types.
Abstract – Several measures have been taken in recent years to reduce the use of fossil fuels and shift toward renewable energy sources such as biomass, particularly cork wastes, which currently generate more than 60% of the energy generated by cork powder energy conversion. This powder’s high calorific content ranging from 4,000 to 7,000 Kcal/kg is natural, renewable, and recyclable, and contributes to a reduction in greenhouse gas emissions and carbon footprint. Cork wastes are now considered strategic substances due to their significant environmental and socioeconomic roles in the worldwide. The present research relies on cork wastes as potential of electrical, thermal, and hydrogen bioenergy source. Cork properties and energy usages are discussed beginning with cork's environmental, economic, and energy properties and processing through two types of cork wates conversion processing: industry and energy process. The firstl one is in four stages: preparation, transformation, granulation, and transformation, whereas the second one has three phases: extraction of cork, storage of planks, and from micro agglomerated cork stoppers to energy generation, and at the end of the study the three types of bioenergy that cork wastes may produce based on recent academic and research discoveries. Electrical energy, thermal energy, and hydrogen energy are the three types